The identification of novel small-molecule inhibitors targeting WDR5-MLL1 interaction through fluorescence polarization based high-throughput screening. Issue 4 (15th February 2019) - Ye, Xiaoqing; Zhang, Rukang; Lian, Fulin; Zhang, Weiyao; Lu, Wenchao; Han, Jie; Zhang, Naixia; Jin, Jia; Luo, Cheng; Chen, Kaixian; Ye, Fei; Ding, Hong
Graphical abstract: Abstract: The protein-protein interaction between WDR5 (WD40 repeat protein 5) and MLL1 (mixed-lineage leukemia 1) is important for maintaining optimal H3K4 methyltransferase activity of MLL1. Dysregulation of MLL1 catalytic function is relevant to mixed-lineage leukemia, and targeting WDR5-MLL1 interaction could be a promising therapeutic strategy for leukemia harboring MLL1 fusion proteins. To date, several peptidomimetic and non-peptidomimetic small-molecule inhibitors targeting WDR5-MLL1 interaction have been reported, yet the discovery walk of new drugs inhibiting MLL1 methytransferase activity is still in its infancy. It's urgent to find other small-molecule WDR5-MLL1 inhibitors with novel scaffolds. In this study, through fluorescence polarization (FP)-based high throughput screening, several small-molecule inhibitors with potent inhibitory activities in vitro against WDR5-MLL1 interaction were discovered. Nuclear Magnetic Resonance (NMR) assays were carried out to confirm the direct binding between hit compounds and WDR5. Subsequent similarity-based analog searching of the 4 hits led to several inhibitors with better activity, among them, DC_M5_2 displayed highest inhibitory activity with IC50 values of 9.63 ± 1.46 µM. Furthermore, a molecular docking study was performed and disclosed the binding modes and interaction mechanisms between two most potent inhibitors and WDR5.